2004
DOI: 10.1136/jnnp.2003.029819
|View full text |Cite
|
Sign up to set email alerts
|

Pontine atrophy precedes cerebellar degeneration in spinocerebellar ataxia 7: MRI-based volumetric analysis

Abstract: Background and objective: Spinocerebellar ataxia 7 (SCA7) is characterised by cerebellar ataxia and visual loss. The aim of the present study was to elucidate the magnetic resonance imaging (MRI) findings characteristic of patients with SCA7. Methods: Twenty patients with SCA (eight SCA3, three SCA6, and nine SCA7) and 20 control subjects underwent an MRI-based volumetric analysis. Results: The pontine volume in patients with SCA7 was decreased by a greater amount than in patients with other types of SCA (p,0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
1
34
1
Order By: Relevance
“…The most affected brain stem structure was the pons, with an average volume reduction of 35.7%. This finding contrast with previous findings reporting only a mild pontine atrophy 13,14 . It is noteworthy that our measurements included part of the cerebellar peduncles and not only the ventral pons, since it is impossible to define the cerebellar anterior limit and brain stem anatomically.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The most affected brain stem structure was the pons, with an average volume reduction of 35.7%. This finding contrast with previous findings reporting only a mild pontine atrophy 13,14 . It is noteworthy that our measurements included part of the cerebellar peduncles and not only the ventral pons, since it is impossible to define the cerebellar anterior limit and brain stem anatomically.…”
Section: Discussioncontrasting
confidence: 57%
“…This divergence increased with another study, which failed to find correlation between CAG expansion and atrophy in a series of SCA1, SCA2 and SCA3 patients 13 . Cerebellar and pontine volume seems to be more involved in SCA7 than in MJD/SCA3 and SCA6, regardless of severity of symptoms or duration of the disease 14 . More recently, the interest have focused on pons and basal ganglia involvement.…”
Section: Machado Joseph Disease: Volumetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…MRIbased volumetric analysis demonstrated that SCA7 patients have significantly more pontine atrophy than patients with other SCAs. Interestingly, it appears that volume loss (as measured by these methods) may develop in the pons prior to the development of cerebellar atrophy, suggesting that the primary site of disease onset may be in brainstem structures rather than in the cerebellar folia (17). Patients with SCA7 develop atrophy of the cerebellar cortex, dentate nucleus, inferior olive, subthalamic nucleus and olivocerebellar, spinocerebellar and pyramidal tracts (18,19).…”
Section: Genetic Features Of Sca7mentioning
confidence: 98%
“…The decrease in saccadic velocity in SCA7 is associated with marked pontine atrophy that characterizes these patients from early stages of the disease and progresses to produce significant external ophthalmoplegia in patients with longer disease history (Bang et al, 2004;Martin et al, 1999). These alterations may precede cerebellar and retinal manifestations and are among the earliest signs of the disease (Oh et al, 2001).…”
Section: Spinocerebellar Ataxia Type 7 (Sca7)mentioning
confidence: 99%